Kepuasan Pengguna terhadap Implementasi Rekam Medis Elektronik Menggunakan Metode EUCS: Tinjauan Literatur - Adi Prabowo; Sinta Novratilova; Amalia Putri Ramadhani; Amalia Sepnesia; Aulia Febiyanti; Bunga Elka Setianingsih; Joao Manuel Correia Ximenes (Jurnal Persada Husada Indonesia, 2026)
Research Objective: This study aimed to describe user satisfaction with electronic medical record (EMR) implementation across the five End User Computing Satisfaction (EUCS) dimensions and to identify commonly reported implementation barriers. Methodology: A structured descriptive literature review was conducted using Google Scholar in April 2026. Searches combined the terms “electronic medical record” OR “rekam medis elektronik,” “End User Computing Satisfaction” OR “EUCS,” and “hospital” OR “rumah sakit.” Indonesian-language, full-text hospital-based studies published from 2022 to 2026 were eligible. Of 1,600 records identified, 5 studies met the criteria and were narratively synthesized. Results: The included studies generally reported favorable satisfaction across content, accuracy, format, ease of use, and timeliness. Nevertheless, recurring concerns were reported for ease of use and timeliness, including difficult workflows, unstable networks, server disruption, system errors, limited user skills, and duplicate data entry. Conclusion: The reviewed evidence suggests that EMR user satisfaction is associated with both system characteristics and implementation conditions. Improvements should prioritize usability, network and server reliability, workflow simplification, and periodic user training.